Biodegradable nasal stents (MgF2‐coated Mg–2 wt %Nd alloy)—A long‐term in vivo study. Issue 2 (29th October 2015) - Durisin, Martin; Reifenrath, Janin; Weber, Constantin M.; Eifler, Rainer; Maier, Hans J.; Lenarz, Thomas; Seitz, Jan‐Marten
Abstract: Despite innovative surgical techniques and use of current frontal sinus stents from different materials, the problem of treatment failure with consecutive reoperation remains present. The aim of our study is to investigate biocompatibility, degradation kinetics, and functionality of a newly developed fluoride‐coated magnesium‐based nasal stent. A minipig anatomy of frontal sinus adapted design and an external surgical approach were developed and established. The functionality of the stents was evaluated endoscopically. The stent‐tissue blocks were analysed after 90 and 180 days using microcomputed tomography (µ‐CT), histology, scanning electron microscopy (SEM), and energy‐dispersive X‐ray spectroscopy (EDS). Functional evaluation revealed an unobstructed stent lumen in all cases. Histological analysis showed moderate mucosal hyperplasia with a mild, nonspecific inflammatory response, and nonosteoconductive effect. Rejection reactions or necrosis did not occur. The volumetric analysis of the stents showed 51% volume loss after 180 days. The EDS analysis did not detect any neodymium (Nd) in the mucosa or bone. The Mg–2 wt % Nd stents are a promising option when treating the narrow passages following paranasal sinus surgery. In particular, its good biocompatibility and good functionality facilitate the re‐epithelization of these constricted passages. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 350–365, 2017.